2001
DOI: 10.1128/mcb.21.23.7933-7943.2001
|View full text |Cite
|
Sign up to set email alerts
|

Individual Somatic H1 Subtypes Are Dispensable for Mouse Development Even in Mice Lacking the H10Replacement Subtype

Abstract: Each of these doubly H1-deficient mice also was fertile and exhibited no anatomic or histological abnormalities. Chromatin from the three double-knockout strains showed no significant change in the ratio of total H1 to nucleosomes. These results suggest that any individual H1 subtype is dispensable for mouse development and that loss of even two subtypes is tolerated if a normal H1-to-nucleosome stoichiometry is maintained. Multiple compound H1 knockouts will probably be needed to disrupt the compensation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
170
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(181 citation statements)
references
References 23 publications
8
170
2
1
Order By: Relevance
“…Expression of the chimeric H1 also led to recruitment of DNMT1 and DNMT3B to the H19 and Gtl2 ICRs, whereas expression of H1c and a truncated H1d lacking this region of the CTD did not lead to recruitment of the two DNMTs. Gene inactivation studies in mice have not revealed essential functions for any of these histone H1 subtypes, including H1c and H1(0) (15)(16)(17). Interestingly however, we reported previously that the genes encoding H1(0) and H1c exhibit differences in their regulation compared with the genes encoding the four other subtypes (40)(41)(42).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Expression of the chimeric H1 also led to recruitment of DNMT1 and DNMT3B to the H19 and Gtl2 ICRs, whereas expression of H1c and a truncated H1d lacking this region of the CTD did not lead to recruitment of the two DNMTs. Gene inactivation studies in mice have not revealed essential functions for any of these histone H1 subtypes, including H1c and H1(0) (15)(16)(17). Interestingly however, we reported previously that the genes encoding H1(0) and H1c exhibit differences in their regulation compared with the genes encoding the four other subtypes (40)(41)(42).…”
Section: Discussionmentioning
confidence: 76%
“…Mammals contain at least eight histone H1 subtypes or variants that differ in amino acid sequences and expression during development (12)(13)(14). Functional differences among these subtypes have been difficult to identify because they appear to act redundantly in development (14)(15)(16)(17). Although the precise location of histone H1 within the chromatin fiber is uncertain, it is known that histone H1 resides outside the nucleosome core particle, where it associates with the DNA as it enters and exits the core particle and protects an additional ∼20 bp of DNA (linker DNA).…”
mentioning
confidence: 99%
“…Furthermore, H1.2 expression is not restricted to Sphase, like the other somatic subtypes (33). Clear is, however, that relocation of H1.2 cannot be essential for mitotic compaction as H1.2 knockout mice develop normally (10). In case there is such a role, other H1 subtypes may have overlapping functions.…”
Section: Discussionmentioning
confidence: 99%
“…The function of having multiple subtypes has not yet been clarified, [for review see (9)]. Although there seems to be a noteworthy redundancy among the histone H1 subtypes (10), evolutionary data indicate that they posses different functional roles (11). They differ in affinity for chromatin (12,13), ability to affect gene regulation (14), and are found to localize to different parts of the nuclei (12).…”
mentioning
confidence: 99%
“…NT 039467) containing exons 9b and 10 was cloned into pBlueScript SK(ϩ). A 2-kb HindIII-HpaI fragment from the plNTK plasmid containing the PGK-Neo cassette surrounded by LoxP1 sites (27) (28). Electroporated cells (10 8 ) were transferred to eight gelatinized plates containing irradiated 40% confluent, G418-resistant feeder cells (leukemia inhibitory factor-expressing STO fibroblasts, American Type Culture Collection).…”
Section: Isolation Of Snf2h Genomic Clones and Preparation Of The Snf2hmentioning
confidence: 99%